Pelatihan Ujaran Kebencian (Hate Speech) Di Media Sosial Terhadap Siswa/I Kelas XI SMA Nurul Hasanah Medan - H Hidayati; A Arifuddin; A Aflina (Jurnal TUNAS, 2021)
The theory of speech act in pragmatics occurs in a communication between speakers and addressees and this is inseparable from the speaking situation during the conversation. Communication at present is not only limited to direct communication between speakers and addressees but also happens globally such as on social media via Youtube, WhatsApp, Twitter, Instagram and Facebook. Social media has a huge influence in people's lives, especially teenagers. Departing from the above problems, the FBK Community Service team provides training and understanding of hate speech to students of class XI at SMA Nurul Hasanah Medan, located on Jalan Jamin Ginting Medan with the aim that they can understand hate speech both from linguistic perspectives and laws on social media. The findings show that students of class XI SMA Nurul Hasanah Medan understand hate speech, especially on social media and also understand the consequences of hate speech on social media and from this understanding it is hoped that social media users can behave and act in accordance with norms and values of communication ethics.